Drivers of tight carbon control in the context of climate change regulation. (22nd December 2017) - Bui, Binh; Chapple, Larelle; Truong, Thu Phuong
Abstract: Our study examines the drivers of tight budgetary control in carbon management in the context of climate change regulation. Using the setting of New Zealand Emissions Trading Scheme (ETS), our study explores how firms manage their carbon performance using carbon‐focused budgetary control. Based on a survey data from New Zealand firms, including both those with and those without an ETS compliance obligations, our results suggest that economic and regulatory environmental pressures, the level of proactiveness of emissions management strategy, the level of integration of carbon issues in strategic and operational processes and the perceived importance of carbon issues are the significant drivers of tight carbon‐focused budgetary control.